Factors associated with oxygenation improvement in children with ARDS - Abdul Chairy; Nurnaningsih Nurnaningsih; Endy P. Prawirohartono (Indonesian Pediatric Society Publishing House, 2014)
Background In pediatric patients, acute respiratory distress syndrome (ARDS) has a high mortality rate of approximately 25%. In surviving children, ARDS may result in sequelae, such as restrictive or obstructive lung dysfunction, muscle weakness and hypotrophy, as well as psychiatric, intelligence, and memory problems. Objective To identify prognostic factors related to oxygenation improvement in children with ARDS. Methods We conducted a prospective cohort study in the pediatric intensive care unit (PICU) ofSardjito Hospital, Yogyakarta. We included 20 children aged 29 days to 18 years who fulfilled the ARDS criteria. They underwent lung recruitment maneuver for 1 hour. Logistic regression analysis was used to assess for possible associations between potential prognostic factors and oxygenation improvement. Results None of the subjec ts had significant hemodynamic changes or hypercapnea during lung recruitment. Two prognostic factors from our univariate analysis, namely type of ARDS (RR 0.17; 95% CI 0.023 to 1.23; P= 0.079) and severity of ARDS (RR 0.74; 95% CI 0.007 to 0.84) , were analyzed by multivariate logression test. However, the results were not statistically significant for type of ARDS (RR 0.33; 95% CI0.009 to 1.41) or severity of ARDS (RR 0.11; 95%CI 0.009-3.25). Conclusion We do not identify any prognostic factors, including type and severity of ARDS, associated with oxygenation improvement in children with ARDS.